On the effect of rolling sphere penetration and rod spacing configurations in optimizing lightning protection for solar farms - Mohd Nasir, Mohd Solehin; Abidin Ab Kadir, Mohd Zainal; Mohd Radzi, Mohd Amran; Azis, Norhafiz; Osman, Miszaina; Farina Mohamad Nasir, Nur Alia (Institute of Electrical and Electronics Engineers, 2025)
Lightning strikes represent a significant threat to solar farms, potentially resulting in equipment damage, power disruptions, and financial losses. This study explores the effectiveness of the Rolling Sphere Method (RSM) as a protective strategy for solar farms, utilizing SESSHIELD-3D lightning simulation software. The analysis focuses on evaluating the effect of penetration values (p=0.3 and p=0.5) and various rod spacing configurations to optimize protection coverage, with air termination rods installed at 0.5 meters on solar panel brackets. The results reveal that penetration value significantly influences shielding efficiency, with p=0.3 demonstrating a greater reduction in unprotected areas compared to p=0.5. Although most of the solar farm is adequately covered, certain red-shaded areas within the structure remain unprotected, highlighting gaps in shielding caused by spacing limitations and penetration effects. A comparative analysis of protected versus unprotected zones indicates that optimizing air termination placement and reducing rod spacing can enhance overall protection coverage. This research contributes to the advancement of lightning protection design for large-scale solar farms, promoting sustainable energy generation while minimizing the risk of lightning-induced failures. The findings offer a framework for cost-effective and efficient protection strategies, balancing safety, performance, and economic feasibility in renewable energy infrastructure.